A study of preschool teachers' perceived stress and their attitudes towards using ICT in teaching young children - Hwong, Chee En (2024)
Teaching has been viewed as a stressful occupation; hence, preschool teachers are frequently reported to struggle striking a balance between work and personal life. Consequently, this will increase stress in general and decrease their attitudes towards using ICT. However, there are still limited research related to preschool teachers’ perceived stress and their attitudes towards using ICT are being discussed in local context. This research aims to study the significant relationship between preschool teachers’ perceived stress and their attitudes towards using ICT in teaching young children in Rawang, Selangor. This study applies the Transactional Model of Stress Thiery and Technology Acceptance Model (TAM) to investigate the correlation ship between teachers’ perceived stress and their attitudes towards using ICT in teaching young children. Quantitative research method and correlational research design are used in this study. Two questionnaires which are Perceived Stress Scale (PSS-10) by Cohen et.al (1998) and Attitudes Scale of Technology Tool Usage In Preschool Education by Kol (2012) are used. Convenient sampling is used and 79 local preschool teachers in Selangor are involved in this study. Descriptive analysis method is used to analyze the descriptive statistics included demographic profiles, mean and standard deviation of stress and job satisfaction, while Statistical Package for the Social Science (SPSS) is used to analyze the inferential statistics. The current finding’s result shows that there is a significant negative relationship between preschool teachers’ perceived stress and attitudes towards using ICT (r=-.539, p>0.001). This study is found limited in the generalizability and sample size. As recommendation, this study suggests extending the generalizability by extend to other states and respondents for analysis and scheduling a better data collection period to improve participation willingness.